Towards a more unified definition of health promotion - Howat, Peter; Maycock, Bruce; Cross, D.; Collins, Jennifer; Jackson, Linda; Burns, Sharyn; James, R. (Australian Health Promotion Association, 2003)
Issues addressed: Health promotion continues to be constrained by the lack of a consistent, clear and useable definition. Discussion: The authors reviewed definitions of health promotion from the international literature and cross-referenced them with the national health promotion competencies and current health promotion practice. The key elements of the most widely used concepts of health promotion have been incorporated into a single definition. A case study has been used to illustrate its practical nature. So what? A clear definition is essential for providing guidance to the scope and nature of health promotion for health promotion practitioners, researchers and their clients. The definition can facilitate planning, implementing and evaluating interventions. In addition, the credibility of health promotion as a professional entity will benefit from a definition that describes uniformity of action.